Biogenic metallic nanoparticles (Ag, TiO2, Fe) as potential fungicides for agriculture: are they safe for the freshwater mussel Anodontites trapesialis? - Tesser, Maria Eduarda; Guilger, Mariana [UNESP]; Bilesky-José, Natália [UNESP]; Risso, Wagner Ezequiel; de Lima, Renata; Martinez, Claudia Bueno dos Reis (Elsevier, 2022)
Silver (Ag), titanium dioxide (TiO2), and iron (Fe) nanoparticles (NPs) synthesized using the fungus Trichoderma harzianum are effective against the agriculture pathogen Sclerotinia sclerotiorum. However, their effects should be evaluated in aquatic organisms, as agriculture practices can contaminate the aquatic environment. Thus, this work evaluated sublethal effects of acute exposure (24 h) to AgNP, TiO2NP and FeNP, synthesized with T. harzianum, on the Neotropical freshwater bivalve Anodontites trapesialis, considering the hypothesis that suspension-feeding bivalves are susceptible to NPs toxicity. Individuals of A. trapesialis were divided into four groups (n = 8/group): a control group, kept in water only; a group exposed to AgNP; a group exposed to TiO2NP; and a group exposed to FeNP. The bioaccumulation of Ag, Ti, and Fe was evaluated in the gills, hemolymph, mantle, digestive gland, and muscle (foot). Lipoperoxidation, activities of the glutathione S-transferase, catalase, and superoxide dismutase, and glycogen concentration were quantified in the gills, mantle, and digestive gland. Ions (Na+, K+, Cl−, Ca2+, and Mg+2) and glucose concentrations were quantified in the hemolymph. Na+/K+-ATPase, H+-ATPase, Ca2+-ATPase, and carbonic anhydrase activities were assessed in the gills and mantle. Acetylcholinesterase activity was determined in the foot and adductor muscle. The mussels exposed to AgNP accumulated Ag in the gills, hemolymph, and foot, and showed a decrease in hemolymph concentrations of Na+ and Cl−, which was associated with the action of Ag ion (Ag+). The exposures to TiO2NP and FeNP led to the accumulation of Ti and Fe in the hemolymph, respectively, but did not promote additional effects. Accordingly, A. trapesialis showed bioaccumulation potential and susceptibility to AgNP, but was not susceptible to TiO2NP and FeNP. Thus, the preferential agricultural use of TiO2NP and FeNP over AgNP is highlighted.
Keywords: Bivalve; Ecotoxicology; Green synthesis; Ionoregulation; Nanoparticles; Pesticides